STATISTIC INVESTIGATIONS OF THE LEVEL OF EDUCATION AS THE COMPONENT OF HUMAN DEVELOPMENT - Назарова, О. Ю.; Чуприн, К. С. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2014)
The article deals with the educational level of the population as one of the most important factors of the economy and culture development of any nation in the world. Modern methodology of UNODP index calculation of the education level is shown. Statistical analysis of the above mentioned factor is given as well as patterns that influence its dunamics concerning the aspects in the world as well as in Ukraine.